Constantine, divine emperor of the Christian golden age - Bardill, Jonathan (Cambridge Univ. Press, 2012)
"Constantine was the first Roman emperor to convert to Christianity. The book explores the emperor's image as conveyed through literature, art, and architecture, and shows how Constantine reconciled the tradition of imperial divinity with his monotheistic faith. It demonstrates how the traditional themes and imagery of kingship were exploited to portray the emperor as the saviour of his people and to assimilate him to Christ. This is the first book to study simultaneously both archaeological and historical information to build a picture of the emperor's image and propaganda. It is extensively illustrated"--Provided by publisher